2006
DOI: 10.1534/genetics.106.059246
|View full text |Cite
|
Sign up to set email alerts
|

Variable Populations Within Variable Populations: Quantifying Mitochondrial Heteroplasmy in Natural Populations of the Gynodioecious PlantSilene vulgaris

Abstract: Populations of mitochondria reside within individuals. Among angiosperms, these populations are rarely considered as genetically variable entities and typically are not found to be heteroplasmic in nature, leading to the widespread assumption that plant mitochondrial populations are homoplasmic. However, empirical studies of mitochondrial variation in angiosperms are relatively uncommon due to a paucity of sequence variation. Recent greenhouse studies of Silene vulgaris suggested that heteroplasmy might occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 53 publications
0
48
1
Order By: Relevance
“…Further evidence of intragenic as well as intergenic recombination in S. vulgaris has recently been shown for several mitochondrial genes (Houliston and Olson 2006;McCauley and Ellis 2008). In addition, data have been shown that are congruent with the idea that heteroplasmy can occur through occasional paternal leakage in S. vulgaris Welch et al 2006), one of the conditions that can yield recombination between variant mitochondrial genomes. Without overestimating the role of recombination in shaping intragenic diversity in Silene mitochondria (see discussion in Barr et al 2007 andEllis 2008), the accumulation of evidence of four-gamete types for several species and genes suggests a common occurrence of this phenomenon in the genus, most likely through past heteroplasmy events.…”
Section: à8mentioning
confidence: 65%
“…Further evidence of intragenic as well as intergenic recombination in S. vulgaris has recently been shown for several mitochondrial genes (Houliston and Olson 2006;McCauley and Ellis 2008). In addition, data have been shown that are congruent with the idea that heteroplasmy can occur through occasional paternal leakage in S. vulgaris Welch et al 2006), one of the conditions that can yield recombination between variant mitochondrial genomes. Without overestimating the role of recombination in shaping intragenic diversity in Silene mitochondria (see discussion in Barr et al 2007 andEllis 2008), the accumulation of evidence of four-gamete types for several species and genes suggests a common occurrence of this phenomenon in the genus, most likely through past heteroplasmy events.…”
Section: à8mentioning
confidence: 65%
“…The most likely mechanism that generates heteroplasmy is paternal transmission of mitochondria, as has been found for Silene vulgaris Welch et al, 2006;Pearl et al, 2009). We checked the mitotypes of progenies from our crosses and found no cases suggesting paternal transmission of mitochondria (unpublished data).…”
Section: Sex Determination In Silene Nutansmentioning
confidence: 74%
“…Documentation of chloroplast heteroplasmy is rare (but see Frey et al, 2005) perhaps due in part to the dogma of strict maternal inheritance in angiosperms. Intraindividual variation has been observed and quantified for plant mitochondrial genes in several cases, (Hattori et al, 2002;McCauley et al, 2005;Welch et al, 2006) but such observations remain rare. Perhaps not surprisingly heteroplasmy occurs if paternal leakage takes place given that the mother presumably always transfers organelles to her offspring.…”
Section: Discussionmentioning
confidence: 99%